Cooperative relations between public higher education institutions: the contextual nature of the process of their creation - Pisarska Aleksandra (Management)
The aim of this study is to recognize the external conditions for establishing cooperative relations between public higher education institutions. At the same time, these conditions constitute the context in which a cooperative relation is or is not established. The article points out that establishing such relations is intentional. It is the external conditions (context) and benefits of adjusting to them that are of key importance for their creation and, in the long run, foe their maintenance. The study focuses on the possibilities of cooperation between public higher education institutions in the legal form of a federation. The study was based on the results of reviewing the literature and current legal acts regulating the higher education system in Poland.